Religiosity and attitudes towards death among older persons in selected barangays of Miag-ao, Iloilo - Edang, Stella Marie
This study aimed to find out if there is a relationship between religiosity and attitudes towards death among older persons. Specifically, this was designed to: 1)measure the level of religiosity of older persons; 2)determine what are the attitudes towards death of older persons; and 3)find out if an older person's religiosity has a relationship with his attitudes towards death. Eighty-eight (88) older persons from selected barangays of Miag-ao were randomly chosen to serve as respondents for this study. The Dejong Religiosity Scale and the Dickstein Attitudes Towards Death Questionnaire were utilized for data gathering., Results showed that older persons generally have high religiosity levels. The mean of scores obtained from the Dejong Religiosity Scale indicates this conclusion (x=133). Their attitudes towards death generally vary. However, the majority of the respondents had expressed generally positive attitudes towards death. this manifested by the mean of scores obtained from Dickstein Attitudes Towards Death Questionnaire (y=66). Moreover, the Pearson-Product Moment Correlation revealed a positive correlation between religiosity attitudes towards death among older persons. This correlation (r=0.11), however, is very weak implying that the relationship is not significant. The researchers recommended that further research should be conducted with the topic under study with a bigger sample for a more valid and reliable results. It would be better if other factors will be considered such as gender differences and social class. Also, it is important to take into consideration how the variables are in the context of the locale of the study.